Relationship Between Work-Life Balance, Role Ambiguity, and Burnout in Generation Z - Karina, Tisa Alif; Suroso; Niken Titi Pratitis (Kirana Publisher (KNPub), 2025)
This research is designed to examine the interrelationships between work-life balance, role ambiguity, and burnout among Generation Z. It aims to investigate how work-life balance correlates with burnout and how role ambiguity contributes to burnout within this demographic. Burnout is defined as a state of mental, emotional, and physical exhaustion resulting from prolonged work pressure. Work-life balance refers to an individual's capacity to strike a healthy balance between job responsibilities and personal life. Role ambiguity occurs when individuals face uncertainty about their job roles, including tasks, duties, and expectations. The study employs three measurement scales: burnout, work-life balance, and role ambiguity. The sample size, derived using the G-power application, consists of 120 Generation Z workers. Multiple regression analysis was applied to the data. The findings indicate a significant relationship between work-life balance, role ambiguity, and burnout in Generation Z. Specifically, a negative relationship was identified between work-life balance and burnout, where lower work-life balance corresponds to higher burnout, and vice versa. Furthermore, a positive correlation was found between role ambiguity and burnout, with higher levels of role ambiguity being linked to increased burnout levels.